2010
DOI: 10.1016/j.jvs.2010.02.257
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year outcomes after endovascular aneurysm repair using earliest available endograft components from a single center

Abstract: Ten-year survival after EVAR parallels that of elective OR but is less than the general population. Although the rate of eventual conversion to open repair was high using this earliest available endograft technology, the aneurysm-related mortality was low, and both endografts remain functional for more than 10 years after placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Population-specific patterns of aneurysm disease can be an explanation and is under investigation, with data being collected from Switzerland, Austria, and Germany. As we continue to follow our patients, we will be curious to see if our results are in accord with the experience of Adiseshiah et al 3 over the long term.…”
supporting
confidence: 80%
“…Population-specific patterns of aneurysm disease can be an explanation and is under investigation, with data being collected from Switzerland, Austria, and Germany. As we continue to follow our patients, we will be curious to see if our results are in accord with the experience of Adiseshiah et al 3 over the long term.…”
supporting
confidence: 80%
“…New generation grafts have low reintervention rates. 14,15 In this study, the majority of reinterventions were performed with low morbidity and mortality using endovascular methods. 16 The two patients who had late open conversion died, which highlights the significant mortality with this technique.…”
Section: Discussionmentioning
confidence: 98%
“…16 The two patients who had late open conversion died, which highlights the significant mortality with this technique. 14,17 Type II endoleaks in the presence of an increase in aneurysm sac size have also been associated with adverse outcomes. 18,19 There was one patient who, despite embolisation of the lumbar artery and attempted embolisation of the circumflex iliac artery, presented with a late rupture.…”
Section: Discussionmentioning
confidence: 99%
“…A 12-year experience of EVAR using earliest available endograft components included only 1 case of endograft sepsis in 50 patients. 7 In a review published in 2010, only 102 cases of abdominal endograft infections had been reported in the literature. 8 The presence of fluid and soft tissue surrounding the stent-graft on CT often prompts such a diagnosis, but a malignant tumor of the aorta or lymphatic tissues, although rare, should also be considered.…”
Section: Discussionmentioning
confidence: 99%